Saturday

April 19, 2014

April 19, 2014

Posted by **maths rockzzz** on Thursday, October 20, 2011 at 8:57am.

- maths -
**Reiny**, Thursday, October 20, 2011 at 9:05amlet f(x) = 2x^4 - 3x^2 + 15x - 15k

if (2x-3) is a factor, then f(3/2) = 0

2(81/16) - 3(9/4) + 15(3/2) - 15k = 0

solve for k

then sub that value into 3k - √5k

**Related Questions**

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

mathssssss - If (2x-3) is a factor of 2x raised to the power four-3xsquare+15x-...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Calculus - relative extrema x^4-2x^2+5 so far I know how to find the derivative ...

Math - Null factor law and factoriising: 2x^2+7x=0 X(2x+7)=0 X=0 or 2x+7=0. ( ...

maths - if sinA+cosA=1/5, then a value of tanA/2 satisfies which of the equation...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

math...up for a challenge? - given that (x+2)s a factor of 2x^3+ 6x^2 + bx - 5 ...

algebra - Factor: 2xy + 6x - 4y - 12 a)(2x + 4) (y + 3) b)(2x - 4) (y + 3)^2 c)(...

algebra - Factor: 2xy + 6x - 4y - 12 a)(2x + 4) (y + 3) b)(2x - 4) (y + 3)^2 c)(...